(untitled) - Besten, P. J. Den (Boca Raton, FL., 2005)
With contributions from leading field experts, this book explores ecotoxicological techniques and methods used for aquatic ecosystem health assessment. The book evaluates bioassay techniques used in the field and includes a detailed discussion of the integration of data, risk communication, and risk perception. The chapter authors analyze how improvements in data processing and information technology have led to the assessment of spatial variability. They cover emerging fields of research such as biomarkers, genome expression, multi-species tests, and tiered approaches. The appendices highlight the strengths and limitations of the techniques and provide references to additional literature.
Keywords: Water quality bioassay,Toxicity testing,Marine ecology,Freshwater ecology